1997
DOI: 10.1136/hrt.78.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bronchopulmonary collaterals and collateral blood flow in patients with chronic thromboembolic and primary pulmonary hypertension.

Abstract: Objective-To compare the visualisation of bronchopulmonary collaterals and bronchopulmonary collateral blood flow in patients with chronic thromboembolic pulmonary hypertension and primary pulmonary hypertension.Setting--Referral centre for cardiology at an academic hospital. Patients-Nine patients with chronic thromboembolic pulmonary hypertension and 17 with primary pulmonary hypertension. Interventions-Bronchopulmonary collaterals were visualised by selective bronchial arteriography or thoracic aortography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 20 publications
3
76
0
7
Order By: Relevance
“…In a rat model of chronic pulmonary artery obstruction, Weibel (28) used a histological approach and documented proliferative changes in bronchial blood vessels with patent new vessels evident by 10 -40 days after LPAL. Furthermore, these results suggested that the response to pulmonary ischemia in the rat more closely resembles bronchial neovascularization in human subjects after pulmonary artery obstruction (6,18). Therefore, the goals of the present study were to confirm the earlier work of Weibel in a rat model of chronic pulmonary ischemia and provide a three-dimensional visualization and functional assessment of the patency of the neovasculature.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…In a rat model of chronic pulmonary artery obstruction, Weibel (28) used a histological approach and documented proliferative changes in bronchial blood vessels with patent new vessels evident by 10 -40 days after LPAL. Furthermore, these results suggested that the response to pulmonary ischemia in the rat more closely resembles bronchial neovascularization in human subjects after pulmonary artery obstruction (6,18). Therefore, the goals of the present study were to confirm the earlier work of Weibel in a rat model of chronic pulmonary ischemia and provide a three-dimensional visualization and functional assessment of the patency of the neovasculature.…”
supporting
confidence: 66%
“…Pulmonary arterial obstruction can lead to abnormalities in gas exchange, to inflammation of lung tissue, and in cases of chronic thromboembolic disease to angiogenesis of systemic bronchial vessels to the ischemic lung (6,18). Models of chronic pulmonary thromboembolism have been developed in a variety of animals.…”
Section: Discussionmentioning
confidence: 99%
“…In human disease, as well as in animal models, obstruction of the pulmonary vasculature results in rapid and sustained systemic neovascularization of the lung (4,6,7,10,18). Both bronchial and intercostal arteries participate by proliferating and perfusing lung vascular networks.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, systemic collateral arterial flow volume can easily be calculated by subtracting the pulmonary arterial flow volume from the pulmonary venous flow volume (Qspa ϭ Qpv Ϫ Qpa). Accurate measurement of systemic collateral flow to the lungs is also useful in differentiating secondary from primary pulmonary hypertension (16,18,19).…”
Section: Clinical Applications Of Mr Quantification Of Pulmonary Venomentioning
confidence: 99%